JADID PHILOSOPHICAL REVIEWS - Najmiddin Ibraimovic Jumamulov (American Journals Publishing, 2025)
The independence of our country has not been easily captured. As Hürrance sewed his life, our crucial ancestors, who had been arrogantly said in the pri'am, was killed in this direction. Similar views about the previous history Bishor finally during this time of the world today, we also contribute to the effectiveness of Murad in the sky of this bladder today.
Keywords: Homeland, national self-government, jadids, freedom, society, theater, third rennesans, enlightenment.